Reconstruction of Contemporary Da'wah Based on Gadamer's Hermeneutics: An Analysis of the Interpretation of QS An-Nisa 4:1 According to Amina Wadud - Siti Nuri Nurhaidah; Muhammad Haris Hakam; Hayatuddin Hayatuddin; Evalinda Evalinda; Muhammad Yudi Ali Akbar (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study explores the interrelation between contemporary Islamic da’wah and Gadamerian hermeneutics through Amina Wadud’s interpretation of Q.S. An-Nisā’ [4]:1, emphasizing the reconstruction of gender understanding in Islamic discourse. Contemporary da’wah is not merely a call to faith but a transformative engagement with social realities, while hermeneutics as articulated by Hans-Georg Gadamer provides a dialogical framework for interpreting sacred texts within historical and cultural horizons. Using a qualitative-descriptive and hermeneutical approach, this research analyzes how Wadud’s interpretive method embodies Gadamer’s concept of the “fusion of horizons” (Horizontverschmelzung), bridging classical Qur’anic exegesis with contemporary gender ethics. The findings reveal that Wadud’s reading reconstructs Q.S. An-Nisā’ [4]:1 as a text affirming the ontological equality of men and women, challenging patriarchal interpretations rooted in pre-modern exegetical traditions. Her interpretation serves as a form of contemporary da’wah a communicative and emancipatory discourse that integrates spirituality, justice, and gender inclusivity. The study concludes that combining Gadamer’s philosophical hermeneutics with Wadud’s feminist Qur’anic reading offers a viable model for renewing Islamic da’wah in the modern era, promoting human dignity and ethical pluralism in the interpretation of divine revelation